2016
DOI: 10.1182/blood-2015-11-680843
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in B-cell development and activation

Abstract: Long noncoding RNAs (lncRNAs) are potentially important regulators of cell differentiation and development, but little is known about their roles in B lymphocytes. Using RNA-seq and de novo transcript assembly, we identified 4516 lncRNAs expressed in 11 stages of B-cell development and activation. Most of these lncRNAs have not been previously detected, even in the closely related T-cell lineage. Comparison with lncRNAs previously described in human B cells identified 185 mouse lncRNAs that have human ortholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 49 publications
(57 reference statements)
7
102
0
2
Order By: Relevance
“…By first separating DLBCL patients of the discovery cohort into either GCB or ABC subtypes based on their clinical information, we performed a comparative analysis for lncRNA expression pattern across GCB and ABC subtypes and uncovered 156 novel differentially expressed lncRNAs associated with either GCB or ABC subtypes. Several recent studies have shown that lncRNA were widely expressed during B-cell development and different lncRNAs played differential functional roles in distinct stages of B-cell development [23, 24]. Our finding has presented evidence that there was differentiated lncRNA expression pattern between GCB and ABC DLBCL, implicating that these subtype-specific lncRNAs may provide additional information for DLBCL subtype classification and prognosis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…By first separating DLBCL patients of the discovery cohort into either GCB or ABC subtypes based on their clinical information, we performed a comparative analysis for lncRNA expression pattern across GCB and ABC subtypes and uncovered 156 novel differentially expressed lncRNAs associated with either GCB or ABC subtypes. Several recent studies have shown that lncRNA were widely expressed during B-cell development and different lncRNAs played differential functional roles in distinct stages of B-cell development [23, 24]. Our finding has presented evidence that there was differentiated lncRNA expression pattern between GCB and ABC DLBCL, implicating that these subtype-specific lncRNAs may provide additional information for DLBCL subtype classification and prognosis.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous work has indicated the prognostic roles of lncRNAs in DLBCL patients [22]. Furthermore, recent studies demonstrated that lncRNA expression patterns can characterize distinct stages of B-cell development and activation [23, 24]. However, the expression pattern and clinical implication of lncRNAs between GCB and ABC DLBCL remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many prior studies of CpG methylomes in adult somatic tissues have found that variably methylated regions are strongly enriched at enhancer sites. Analysis of publicly available ChIP-Seq data for H3K4me1 and H3K4me3 modifications in mature B2 and B1 B cells 22 , showed that the DMRs that underwent developmental demethylation in both B1 and B2 B cells colocalized with H3K4me1 peaks in mature B1 and B2 B cells, suggesting that these DMRs might represent developmentally demethylated enhancers that modulate lineagespecific gene expression ( Figure 2C). To assess the significance of these enhancers in the context of hematopoietic development, we also examined H3K4me1 and H3K4me3 marks in HSCs using published ChIP-Seq data.…”
Section: Programmed Demethylation In B1a B Cells Occurs At Enhancers mentioning
confidence: 99%
“…We obtained H3K4me1, H3K4me3 ChIP-Seq data in B1 and B2 cells (GSE72017) and H3K4me1 ChIP-Seq data in mouse HSCs (GSE63276) from the NCBI GEO database 22,67 . The ATAC-Seq libraries were generated and sequenced in our laboratory as previously described 40 .…”
Section: Chip-seq and Atac-seq Analysismentioning
confidence: 99%
“…It has been shown that many lncRNAs are present in neutrophils and the levels of lncRNA expression are associated with development, differentiation and activation of neutrophils [72,73]. Furthermore, previous studies have identified lncRNAs expressed in B lymphocytes and T lymphocytes development and activation [74,75]. Panzeri et al suggested that long intergenic non-coding RNAs could be novel drivers of human lymphocyte differentiation [76].…”
Section: Lncrnas Involved In Inflammation After Scimentioning
confidence: 99%